Cooperation between the Doctor and Nursing Staff in the Proces of Diagnosis and Thrombolytic Treatment of Patients in Acute Stroke Period - Anna Żdanowicz; Małgorzata Wiszniewska; Mariusz Domagalski (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
In accordance with the WHO (World Health Organization) definition applicable since 1980, stroke (BS) is a disease syndrome characterized by a sudden occurrence of focal or generalized cerebral dysfunctions, which last longer than 24 hours, unless they are fatal. Thrombolytic therapy is currently the recommended and most effective method of treatment of recent ischemic stroke. The success of treating stroke equally depends on the appropriate organization of the entire team caring for the patient. In order to efficiently conduct thrombolytic treatment in a patient with acute ischemic stroke, medical and nursing staff working in the Department of Stroke Treatment should have the following skills: high level of professional responsibility, high professional competence, have the ability to cooperate in a team and establish interpersonal contacts, including those with the patient and their family. Team members should make difficult decisions jointly, analyze and modify their activities so that treatment could be implemented as soon as possible while maintaining the utmost discretion and clinical alertness. This article was prepared in order to summarize and organize available knowledge on the cooperation between the doctor and nursing staff in the diagnosis and thrombolytic therapy of patients in the acute stroke period. (JNNN 2019;8(1):37–43)